Temporomandibular Disorders in Patients with Occlusal Interferences - Sharif, Mubashir; Amjad, Amna; Hussain, Sajjad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the temporomandibular disorders among patients with occlusal interferences. Study Design: Cross-sectional study. Place and Duration of Study: Prosthodontics Department, Armed Force Institute of Dentistry, Rawalpindi Pakistan, from Jul to Dec 2020. Methodology: Consecutive patients presenting with symptoms of occlusal interferences, including pain, clicking and limited mouth opening to the prosthodontics department, were included in the study. History was taken from each patient, and a detailed oral checkup was done to evaluate the presence or absence of TMDs in patients with occlusal interferences after informed consent. Results: The mean age was 30.44±5.95 years. Out of 380 patients with occlusal inferences, 208(54.7%) patients were diagnosed with temporomandibular disorders. No significant difference was found in the distribution of TMDs with regard to age (p=0.559) and gender (p=0.755). Conclusion: The presence of temporomandibular disorders among patients with occlusal interferences was quite common.This presence is equally common in different age groups and both genders. Keywords: Balancing interferences, Occlusal interferences, Protrusive interferences, Temporomandibular joint, Temporomandibular disorders,